Achieving mainstream nitrogen removal through simultaneous partial nitrification, anammox and denitrification process in an integrated fixed film activated sludge reactor. (July 2018) - Wang, Chao; Liu, Sitong; Xu, Xiaochen; Zhang, Chaolei; Wang, Dong; Yang, Fenglin
Abstract: The anaerobic ammonium oxidation (anammox) is becoming a critical technology for energy neutral in mainstream wastewater treatment. However, the presence of chemical oxygen demanding in influent would result in a poor nitrogen removal efficiency during the deammonification process. In this study, the simultaneous partial nitrification, anammox and denitrification process (SNAD) for mainstream nitrogen removal was investigated in an integrated fixed film activated sludge (IFAS) reactor. SNAD-IFAS process achieved a total nitrogen (TN) removal efficiency of 72 ± 2% and an average COD removal efficiency was 88%. The optimum COD/N ratio for mainstream wastewater treatment was 1.2 ± 0.2. Illumina sequencing analysis and activity tests showed that anammox and denitrifying bacteria were the dominant nitrogen removal microorganism in the biofilm and the high COD/N ratios (≥2.0) leaded to the proliferation of heterotrophic bacteria ( Hydrogenophaga ) and nitrite-oxidizing bacteria ( Nitrospira ) in the suspended sludge. Network analysis confirmed that anammox bacteria ( Candidatus Kuenenia) could survive in organic matter environment due to that anammox bacteria displayed significant co-occurrence through positive correlations with some heterotrophic bacteria ( Limnobacter ) which could protect anammox bacteria from hostile environments. Overall, the results of this study provided more comprehensive information regarding the community composition and assemblies in SNAD-IFAS process for mainstream nitrogen removal. Graphical abstract: Highlights: SNAD-IFAS process was feasible for mainstream nitrogen removal. The optimum COD/N ratio for mainstream nitrogen removal by SNAD-IFAS was 1.2 ± 0.2. Biodiversity of heterotrophic bacteria and NOB both increased with COD increasing. Anammox displayed significant co-occurrence with some heterotrophic bacteria.